1980
DOI: 10.1128/jvi.36.1.103-108.1980
|View full text |Cite
|
Sign up to set email alerts
|

Suppressors of mutations in the bacteriophage T4 gene coding for both RNA ligase and tail fiber attachment activities

Abstract: The protein product of T4 gene 63 catalyzes both the attachment of tail fibers to fiberless phage particles and the ligation of single-stranded RNA (Snopek et al., Proc. Natl. Acad. Sci. U.S.A. 74:3355-3359, 1977). To investigate whether the gene 63 product has a role in nucleotide metabolism, we isolated false revertants

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…hus mutants grow poorly in the presence of hydroxyurea, while the growth of Rid394 depends on the allelic state of the host rho gene, whose product modulates transcription termination; these traits are considered in Discussion. The locations of most of the t mutations agree with previous mapping studies (11,13,38), except that Rid394 does not sequence to the predicted position (26) and the order of amA3 and amB5, while consistent among all later maps, is reversed from that given in the canonical report (15); the amber mutants may have been reversed when originally archived, or the original mapping may have employed too few mutants to secure the order correctly.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…hus mutants grow poorly in the presence of hydroxyurea, while the growth of Rid394 depends on the allelic state of the host rho gene, whose product modulates transcription termination; these traits are considered in Discussion. The locations of most of the t mutations agree with previous mapping studies (11,13,38), except that Rid394 does not sequence to the predicted position (26) and the order of amA3 and amB5, while consistent among all later maps, is reversed from that given in the canonical report (15); the amber mutants may have been reversed when originally archived, or the original mapping may have employed too few mutants to secure the order correctly.…”
Section: Resultssupporting
confidence: 79%
“…Additional sequencing confirmed that none of the three tr mutants contain mutations in the distant rI gene (whose mutations are phenotypically identical to rV mutations). We next sequenced all of the previously mapped t mutants (11,13,26), with the results shown in Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A65T (5tsDH6318) has been isolated as a pseudo-revertant of the gene 63 − mutant. Gp63 has a function to facilitate tailfiber attachment, and A65T is a bypass mutant of gene 63 deletion (Hall et al 1980). The mechanism of the bypass function is not known.…”
Section: Tail Lysozyme Gp5mentioning
confidence: 99%
“…There are a number of mutants with distinct phenotypes which have a mutation in gene 5 (4,6,20). All the mutation sites were recently determined by sequencing the genomic DNA from each mutant (15).…”
mentioning
confidence: 99%